Training of the Art Reading Al Qur'an of Sidomulyo Community at Tumbang Tahai Village - Satria Nur Rizki; Nurul Wahdah; Muslimah (Yayasan Payungi Smart Madani, 2022)
The art of reading the Qur’an is the art of reading that is sung to the rhythm of thesong. This art is known as An-Nagham fil Qur’an (Beauty reading of the Qur’anaccording to its rules). Meanwhile, the object of Nagham’s knowledge is to learnthe method, method of humming or singing the recitation of the Qur’an. The art ofreading the Qur’an will be easy to understand if someone can learn the art ofreading, has mastered theory of the art of song well, understand the science ofrecitation, and can read the Qur’an with tartil. In addition, there are also mainaspect that must be mastered by someone to be perfect in the art of reading the Qur’an, namely mastery of breath, voice, fashahah, and adab. The method used in this service is ABCD (Asset Based Community Development) method. This methodhas the main focus, namely broadcasting the Qur’an with the development ofcommunity assets through the art of the reading Qur’an. This coaching activityaims to increase the potential of the community in the art of reading the Qur’an(Nagham fil Qur’an). This coaching activity aims to increase the knowledge andpotential of the community in understanding the art of reading the Qur'an(Nagham fil Qur'an). This activity was carried out for four months and wasattended by 14 participants consisting of four children, four teenagers, and sixmothers